South Korean male footballers' involuntary labor migration: Why do they leave for Southeast Asia? - Wangsung Myung (Korea Institute of Sport Science, 2021)
Purpose This study aims to explore migration factors of Korean male footballers who have moved from South Korea to Southeast Asian countries. Methods Qualitative case study was conducted with 9 footballers, 4 their agents and 2 K-league staffs as the participant. Results As a result, by regarding their migration as involuntary decision, this study could provide academic and practical discussion on sport labor migration. First of all, this study established theoretical framework for involuntary migration of the participants through 'Push-Pull Theory' which focuses on demand and supply on the labor force. Second, this study found that a local rule (FA compensation system) of Korean professional football league (K league) and hierarchical collectivist culture contributed to their migration, which has not been reported by previous studies focused on the voluntary migration of mainstream players and it reflected local context of K league. Conclusions In conclusion, this study confirmed that sport labor migration was also considered as social phenomenon and reflected a cross section of a particular society. Through the migration of athletes, we can provide a variety of viewpoint on economic (market) structure, related policy and system in a particular society, and understand migration motives in terms of agency (subculture).